Posttraumatic growth and adjustment to spinal cord injury: moderated by posttraumatic depreciation? - Kunz, Simon; Joseph, Stephen; Geyh, Szilvia; Peter, Claudia (American Psychological Association, 2016)
Objective: Findings on the relationship of posttraumatic growth (PTG) with adjustment to potentially traumatic events are inconsistent, whereupon posttraumatic depreciation (PTD) has been suggested as a possible moderator. The objective of this study is to investigate the associations between PTG and PTD on one side and life satisfaction and indicators of mental and physical health on the other side in individuals with spinal cord injury (SCI). The primary study aim is to test whether PTD moderates the relationships of PTG and different adjustment indicators. Method: A total of 141 patients administered to one of four Swiss SCI rehabilitation centers completed questionnaires assessing PTG and PTD, different indicators of mental and physical health as well as life satisfaction at discharge from first rehabilitation. Correlational and regression methods were used to examine the research question. Results: PTG and PTD were significantly positively correlated (rs = .47). PTD was significantly associated with lower mental and physical health and lower life satisfaction, with small to large effect sizes. PTD moderated the associations of PTG with symptoms of depression and life satisfaction (β of interaction term = -.18 and .24, respectively). PTG was significantly related to lower levels of symptoms of depression and higher life satisfaction in individuals experiencing moderate to high levels of PTD. In contrast, PTG was not significantly related to these outcomes in individuals with low PTD levels. Conclusion: The neglect of PTD in research partially explains mixed findings on the relationship of PTG and adjustment to potentially traumatic events. Keywords: